Development of an Interactive Digital Learning Media “E-MIREDOKS” on Redox Reaction Material - Aisyah Verolita Firdauz; Sukarmin Sukarmin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This study aims to develop and evaluate the feasibility of E-MIREDOKS (Redox Reaction Interactive E-Module) as a digital and interactive learning tool for teaching redox reactions in chemistry. The research methodology employed is the Research and Development approach developed by Sukmadinata, which involves three main stages: preliminary study, media development, and media testing, culminating in a limited-scale trial. This methodology was chosen due to its alignment with the goal of developing a learning tool. The validity of the developed medium was assessed using validity sheets, pretest and posttest sheets, student feedback, and observation sheets. The medium was found to be feasible based on its content and construct validity, with validity percentages of 85.56% and 85.93% respectively, falling within the category of exceptionally valid. The effectiveness of the medium was evaluated through a comparison of pretest and posttest scores, resulting in a sig.(2-tailed) value of 0.00 < 0.05 (α), indicating a significant difference in mean scores between the pretest and posttest. Out of 36 students, 31 achieved individual learning accuracy, while 86.11% attained classical learning accuracy. The practicality of the medium was assessed using student feedback, which yielded a percentage of 92.63%, and observations of student behavior, which scored 96.67%, both falling within the category of exceptionally practical. These findings provide evidence that E-MIREDOKS can serve as an effective digital and interactive learning tool for chemistry education.